Entering the era of highly effective modulator therapies. (12th January 2021) - Dave, Kavita; Dobra, Rebecca; Scott, Sandra; Saunders, Clare; Matthews, Jess; Simmonds, Nicholas J.; Davies, Jane C.
Abstract: Since the discovery of the gene responsible for cystic fibrosis (CF) in 1989, hopes have been pinned on a future with novel therapies tackling the basis of the disease rather than its symptoms. These have become a reality over the last decade with the development through to the clinic of CF transmembrane conductance regulator (CFTR) modulators. These are oral drugs which improve CFTR protein function through either increasing the time the channel pore is open (potentiators) or facilitating its trafficking through the cell to its location on the cell membrane (correctors). The first potentiator, ivacaftor, is now licensed and available clinically in many parts of the world. It is highly effective with impressive clinical impact in the lungs and gastrointestinal tract; longer‐term data from patient registries show fewer exacerbations, a slower rate of lung function loss and reduced need for transplantation in patients receiving ivacaftor. However, as a single drug, it is suitable for only a small minority of patients. The commonest CFTR mutation, F508del, requires both correction and potentiation for clinical efficacy. Two dual‐agent drugs (lumacaftor/ivacaftor and tezacaftor/ivacaftor) have progressed through to licensing, although their short term impact is more modest than that of ivacaftor; this is likely due to only partial correction of protein misfolding and trafficking. Most recently, triple compounds have been developed: two different corrector molecules (elexacaftor and tezacaftor) which, by addressing different regions in the misfolded F508del protein, more effectively improve trafficking. In addition to large improvements in clinical outcomes in people with two copies of F508del, the combination is sufficiently effective that it works in patients with only one copy of F508del and a second, nonmodulator responsive mutation. For the first time, we thus have a drug suitable for around 85% of people with CF. Even more gains are likely to be possible when these drugs can be used in younger children, although more sensitive outcome measures are needed for this age group. Special consideration is needed for people with very rare mutations; those with nonmodulatable mutation combinations will likely require gene or messenger RNA‐based therapeutic approaches, many of which are being explored. Although this progress is hugely to be celebrated, we still have more work to do. The international collaboration between trials networks, pharma, patient organizations, registries, and people with CF is something we are all rightly proud of, but innovative trial design and implementation will be needed if we are to continue to build on this progress and further develop drugs for people with CF.